Case Report: Bi-allelic missense variant in the desmocollin 3 gene causes hypotrichosis and recurrent skin vesicles - Al Hawsawi, Khalid; Al Jabri, Mazin; Dajam, Mazen S.; Almahdi, Bashaer; Alhawsawi, Waseem K.; Abbas, Safdar; Al Tuwaijri, Abeer; Umair, Muhammad; Alfadhel, Majid; Al-Khenaizan, Sultan (Frontiers in Genetics, 2022)
Abstract Background: Hypotrichosis with Recurrent Skin Vesicles (HYPTSV) is an extremely rare condition, having autosomal recessive inheritance. Here, we report a 4-year- old Saudi boy who presented with a history of recurrent skin blisters localized to the extremities and hypotrichosis since birth. Methods: The present study describes a consanguineous Saudi family segregating HYPTSV in an autosomal recessive fashion. A single proband (II-1) exhibited features such as diffused non-scarring alopecia on the scalp, intraepidermal blister, post-inflammatory hyperpigmented macules, and follicular hyperkeratosis. DNA of the index was subjected to whole-genome sequencing (WGS). Furthermore, 3D protein modeling was performed for the mutated and normal protein. Results: WGS revealed a novel bi-allelic missense variant [c.154G>C; p.Val52Leu] in the DSC3 gene, segregating perfectly using Sanger sequencing. In addition, 3D protein modeling revealed a substantial change in the mutated DSC3 protein compared to the normal DSC3 protein. Conclusion: This is the 3rd novel variant reported in the DSC3 gene that canbe associated with the HYPTSV phenotype. This report further strengthens the evidence that bi-allelic variants in the DSC3 might cause severe HYPTSV in humans.